EFFECTS OF BURNING AND GRAZING ON PLANT SPECIES PERCENTAGE COVER AND HABITAT CONDITION IN THE HIGHLAND GRASSLAND OF MPUMALANGA PROVINCE, SOUTH AFRICA - M. K. Boakye; I. T. Little; M. D. Panagos; R. Jansen (Journal of Animal and Plant Sciences, 2013)
Fire and grazing have long been used as a grassland management tool in South Africa for livestock production. Despite the ecological importance of fire and grazing to the grassland ecosystem, the appropriate use of fire and grazing as a land use management tool has been questioned. The effects of different burning frequencies and stocking rates on species composition were studied between January and March 2008 using a Modified-Whittaker design in commercial farms, communal land and a nature reserve stocked with game herbivores in the highland grassland of Mpumalanga Province of South Africa. The results revealed that species assemblages of an annually burned site were completely dissimilar from a biennially burned site. The annually burned site was dominated by flora that is considered as fire-tolerant species. In contrast, the protection of some areas from burning in addition to regular burning of other areas ensured the presence of both fire-tolerant and fire-intolerant species and contributed to the high species composition of communal land. This study therefore suggests that biennial burning, or even longer intervals of burning of grazed land in addition to partial or mosaic burning should be employed to enhance the biodiversity conservation status of these montane grasslands.
Keywords: fire; grazing; highland grassland; herbivores